2016
DOI: 10.3390/ijerph13111067
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Obesity as Independent Risk Factors for Osteoporosis: Updated Results from the ROIS/EMEROS Registry in a Population of Five Thousand Post-Menopausal Women Living in a Region Characterized by Heavy Environmental Pressure

Abstract: Objectives:We aimed to analyze bone mineralization and the effect of different risk factors for osteoporosis in postmenopausal women. Methods: We found 4909 postmenopausal subjects within ≥10,000 records from the ROIS/EMEROS (Ionian and Salento Osteoporosis Registry/Euro Mediterranean Registry of Osteoporosis) registry, a population study carried out in an area characterized by heavy environmental pressure between Brindisi and Taranto from 2009 to 2016. All subjects were assessed via phalangeal quantitative ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…In the current study, we found that adults with CP had a higher prevalence of fracture across all regions of the body compared with adults without CP. We also found that the odds of any fracture was more than 2 times higher among adults with CP, even after adjusting for cardiometabolic diseases, which are more prevalent in the adult CP population and are associated with skeletal fragility in the non‐CP population . Another important factor for fracture risk is osteoporosis.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In the current study, we found that adults with CP had a higher prevalence of fracture across all regions of the body compared with adults without CP. We also found that the odds of any fracture was more than 2 times higher among adults with CP, even after adjusting for cardiometabolic diseases, which are more prevalent in the adult CP population and are associated with skeletal fragility in the non‐CP population . Another important factor for fracture risk is osteoporosis.…”
Section: Discussionmentioning
confidence: 70%
“…We also found that the odds of any fracture was more than 2 times higher among adults with CP, even after adjusting for cardiometabolic diseases, which are more prevalent in the adult CP population (30) and are associated with skeletal fragility in the non-CP population. (42,43) Another important factor for fracture risk is osteoporosis. We have previously reported that the prevalence of osteoporosis is similar among young adults with CP (18 to 30 years) as compared with the general population of adults !50 years of age, (35) and becomes progressively more prevalent throughout the adult CP lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average performance from two trials using the participants' dominant hand was used as the result for analysis. Since lifestyle is important to physical and health status [18][19][20], information on alcohol drinking (≥ 40 g/day in men, ≥ 20 g/day in women), current smoking (yes/no), exercise (at least 30 min twice per week), and menopause (yes/no only in women) was collected by interview.…”
Section: Methodsmentioning
confidence: 99%